ANALISA THROUGHPUT JARINGAN 4G LTE DAN HASIL DRIVE TEST PADA CLUSTER RENON - I Dw Gd Paramartha Warsika; N.M.A.E. Dewi Wirastuti; Pande Ketut Sudiarta (Program Studi Teknik Elektro UNUD, 2019)
The development of very rapid communication technology specifically on 4G networks. cannot be separated from various problems, one of which is the occurrence of traffic density which causes transmission data rate decline.Telecommunications services in particular throughput has increased access. From this problem, this paper studies the simulation results of 4G LTE network throughput compared to the results of the drive test on the renon cluster. From the simulation, it known that the coverage area of 1.31 km2 and the speed of data access are termed by the equipment user 4,000 kbps to 5,000 kbps. While the results of drive test analysis using G-NetTrack Pro software with dedicated method from the existing eNodeB AKABA_PL, MYAMIN_CR, and BUNDARANRENON_PL data. The average downlink obtained by users is 2 Mbps, distance 100 to 800 meters that can be drawn on each sector eNodeB. The parameters measured are RSRP, RSRQ, SINR and throughput. Analysis of the drive test results found parameters that affect access speed when downloading and several other factors. Furthermore, the parameters of the downlink throughput was compared to the simulation results with the measurement data in the field and from the comparison made the results are linear.